Use of the virtual class (VC) application: a survey among students - Salleh, Arfah; Minai, Badriyah (Universiti Putra Malaysia Press, 2002)
This study investigates the use of the virtual class (VC) application by accounting students at the Faculty of Economics and Management (FEM). Two main issues examined are the pattern of usage by students and their suggestions to improve the usefulness of the application for their learning process. The study shows that among the six modules of the VC application offered at the FEM, the "Assignment and Quizzes" module was used most frequently by students in the Intermediate Accounting course. There were students who viewed the VC application as an opportunity to be absent from lectures. The length of time spent in accessing the VC application is cited as the main problem in using the application. The major benefits of using the VC application include its ability to enhance the students' knowledge of a course and assist students to communicate with lecturers. A majority of the students maintain that VC application should be extended to all lecturers in the university. Suggestions given to improve usage of VC application include improvement of on-eampus facilities and provision of more complete sets of notes than currently available.